1994
DOI: 10.1093/bja/73.4.503
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy in adults: effects of extracranial ischaemia and intracranial hypoxia on estimation of cerebral oxygenation

Abstract: We have studied the effects of extracranial ischaemia and intracranial hypoxia on measurement of cerebral oxygenation using near-infrared, reflectance-mode, cerebral oximetry (Invos 3100 cerebral oximeter) in healthy adult subjects. Under stable systemic conditions, scalp ischaemia induced by a pneumatic tourniquet caused an apparent reduction in mean regional cerebral oxygenation (rSO2) from mean 72 (SD 6)% to 59 (7)% (n = 8, P < 0.001). rSO2 returned to control values within 1 min of release of the tournique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
1
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(86 citation statements)
references
References 0 publications
6
77
1
2
Order By: Relevance
“…26 The lack of correlation between TOI and PaCO 2 is consistent with the studies of Germon et al 22,27 Using another NIRS machine (INVOS 3100@) device, they were not able to detect changes in cerebral oxygenation as a result of cerebral hyperemia due to hypercapnia. By contrast, Tateishi et al 28 studied nine patients with head trauma and found that the direction and magnitude of changes in cerebral oxyhemoglobin concentration measured by NIRS and SjO 2 in response to changes in PaCO 2 were similar in eight of the patients.…”
Section: Discussionsupporting
confidence: 79%
“…26 The lack of correlation between TOI and PaCO 2 is consistent with the studies of Germon et al 22,27 Using another NIRS machine (INVOS 3100@) device, they were not able to detect changes in cerebral oxygenation as a result of cerebral hyperemia due to hypercapnia. By contrast, Tateishi et al 28 studied nine patients with head trauma and found that the direction and magnitude of changes in cerebral oxyhemoglobin concentration measured by NIRS and SjO 2 in response to changes in PaCO 2 were similar in eight of the patients.…”
Section: Discussionsupporting
confidence: 79%
“…However, the contamination of signal from extracranial tissue has been of concern for some time. 16 Further, inherent difficulties in the implementation of NIRS techniques in the context of brain injury exist, which have inhibited the widespread introduction of NIRS techniques for these patients (such as scalp and facial injuries and the presence of hematomas). With current methods, the baseline reading obtained for rSO 2 is highly variable, and rarely gives an accurate absolute value.…”
Section: Near-infrared Spectroscopy In Tbimentioning
confidence: 99%
“…Therefore, what is more useful in all clinical scenarios is to monitor the trend in terms of deviation from the baseline rSO 2 levels. In the traumatically injured brain the variability in baseline saturation readings is even greater, 2,15,16 because of loss of normal cerebral vascular autoregulation, and the subsequent changes from this baseline are more difficult to interpret. This, combined with the frequent presence of subdural, epidural, and extracranial hematomas that further confound saturation signals, has prevented NIRS-based observation in TBI from becoming widespread and routine.…”
Section: Near-infrared Spectroscopy In Tbimentioning
confidence: 99%
“…22 Increasing the distance between photoprobes is thought to reduce the interference of extracranial factors. 23 Kirkpatrick et al reported that interruption ofextracranial blood flow by clamping the external carotid artery had no effect on NIPS measurement. 14 In our study, we utilized the new probe which had a long emitter-detector distance, and facial muscle activities were completely blocked by muscle relaxant.…”
Section: Discussionmentioning
confidence: 99%